2018
DOI: 10.17549/gbfr.2018.23.2.66
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Climate Change Risk and Cost of Capital

Abstract: In recent years, a global consensus has emerged on the importance of climate change risks. Climate change risk is also known to affect investment decision-making processes, such as those related to the issuance of Green Bonds and the use of ESG investment principles. Given this context, we examine whether there is a relationship between the cost of capital and climate change risk, by focusing on companies under the Target Management Scheme in Korea. Companies with high levels of greenhouse gas emissions or ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Additionally, this study focused on identifying potential solutions for improving blockchain adoption for the foodservice industry by addressing how negative associations with blockchain resistance can be minimized. Drawing on the stakeholder theory, “public pressures” and “climate change awareness” were investigated to assess their potential roles as moderators in mitigating the negative effect of “blockchain resistance” on “adoption intentions.” Pressures associated with internal and external stakeholders play important roles in leading organizations to go green (Hyatt and Berente, 2017; Noh, 2018). These findings are well supported in the current study, demonstrating the significant roles of internal and external stakeholders in weakening the negative relationship between blockchain resistance and adoption intentions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this study focused on identifying potential solutions for improving blockchain adoption for the foodservice industry by addressing how negative associations with blockchain resistance can be minimized. Drawing on the stakeholder theory, “public pressures” and “climate change awareness” were investigated to assess their potential roles as moderators in mitigating the negative effect of “blockchain resistance” on “adoption intentions.” Pressures associated with internal and external stakeholders play important roles in leading organizations to go green (Hyatt and Berente, 2017; Noh, 2018). These findings are well supported in the current study, demonstrating the significant roles of internal and external stakeholders in weakening the negative relationship between blockchain resistance and adoption intentions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, thanks to the improved environmental risk exposure, firms may take advantage of the cost of debt reduction and the increase of debt capacity with related tax benefits. Park and Noh (2018) focused on a sample of firms under the Target Management Scheme in Korea and analysed the relationship between climate change risk (measured in terms of GHG emissions and energy consumption) and the WACC. The authors found that companies with a higher risk linked to climate change, suffer from a higher cost of capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Park and Noh (2018) focused on a sample of firms under the Target Management Scheme in Korea and analysed the relationship between climate change risk (measured in terms of GHG emissions and energy consumption) and the WACC. The authors found that companies with a higher risk linked to climate change, suffer from a higher cost of capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The aim of this work is to study whether climate risks significantly affect the systematic risk coefficient (beta) of companies operating in the oil and gas sector through the application of econometric models, as described earlier. The main reference articles that supported the definition of the models were Sharfman and Fernando (2008), Trinks et al (2017) and Park and Noh (2018).…”
Section: A the Model And Its Variationsmentioning
confidence: 99%